The Exploring Interaction in an English-Speaking Class for Working Accounting Students - Occe Luciana; Muhammad Hilmi Syauqi (Jurnal Pembelajaran dan Riset Pendidikan, 2026)
This study explored classroom interaction patterns in an English-speaking class for working Accounting students at STIE Wibawa Karta Raharja. Using a descriptive qualitative design, the study examined lecturer-student and peer interaction during classroom activities. The participants consisted of three working students attending evening classes. Data were collected through classroom observation and field notes. The findings showed that supportive classroom interaction helped maintain student participation despite fatigue, irregular attendance, and limited learning time. Positive lecturer responses and flexible communication strategies also contributed to a more comfortable speaking environment for the students.